PENGARUH TATA KELOLA PERUSAHAAN, CASH HOLDINGS, DAN MODEL BISNIS TERHADAP NILAI PERUSAHAAN - Kukuh Herwibawa; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the relationship between Corporate Governance, Cash Holdings, and Business Models on Firm Value in financial companies in Indonesia. Corporate Governance is divided into three sections Board Size, Independent Directors, and Audit Quality.The population in this study are all companies listed on the Indonesia Stock Exchange for 2017 - 2019. The sampling method used in this study is purposive sampling. The number of samples used in this study were 76 research samples. The data used in this study were obtained from the company's annual report. The data in this study were analyzed using multiple regression techniques. This study uses purposive sampling by taking financial sector companies listed on the BEI.. The results of this study that Board Size and Independent Directors had not significant on firm value. Audit Quality, Cash Holdings, and Business Models significant on firm value.